Socialization Of Improving Bumdes Financial Management In Indonesia - Sasongko, Restu Widyo (Universitas Pahlawan Tuanku Tambusai, 2024)
When researchers held in-depth discussions with officials from the Baros Village-Owned Usha Agency, West Java. They complain about good financial management, how to get financing, upgrade financing, etc. The conclusion of this article show 1. Financial management is vital and urgent to improve the financial performance of a company and other institutions, including Village-Owned Enterprises. 2. This service was carried out at the Baros Village-Owned Enterprise, West Java, which began with complaints from the Village-Owned Enterprise and the author's findings regarding reporting that was not yet systematic, difficult to find independent financing, and not carrying out evaluations.3. The author conducted socialization on how to manage finances well for two weeks. Especially regarding simple openings consisting of business evaluation/analysis, reporting and bookkeeping which the author believes can overcome these problems.